PENGARUH MOTIVASI, GAYA KEPEMIMPINAN TRANSAKSIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PT. NJONJA MENEER - Pranantiyo, Shani; Hidayat, Wahyu; Widiartanto, Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2015)
This research is motivated by the increasingly strict business world, accompanied by the times that requires every manufacturer to be able to improve the performance of each employee. One of the products that can be affected by the times are herbs. Herbal products become one of the favorite alternative medicine in Indonesian society given the herbal raw material and has become an entity of hereditary tradition. However, in the period 2010-2013 year results that employee performance production departement of PT. Njonja Meneer Semarang fluctuated. If this is not addressed then feared PT. Njonja Meneer Semarang can not meet the needs of the market and the popularity of herbal medicine will be replaced by other manufacturers.            The purpose of this study was to determine the effect of motivation, transactional leadership styles and organizational culture on employee performance of production of PT. Njonja Meneer Semarang. This research method is explanatory, with data collection through questionnaires and interviews. The sampling technique used purposive technique sampling. The samples are 90 peoples whom are employees of the production departement of PT. Njonja Meneer Semarang. The analysis technique used was qualitative and quantitative. Quantitative analysis using validity, reliability, cross tabulation, correlation coefficient, coefficient of determination, simple and multiple regression analysis, as well as the significance test (t test and F test).            The results of this study showed All independent variables, namely motivation (X1), transactional leadership style (X2), and organizational culture (X3) together (simultaneously) or individually (partial) affect employee performance dependent variable (Y). Advice can be given that the need for the physical layout of a good and convenient for employees as the embodiment of a strong organizational culture of the company. In addition, companies need to provide training for employees and distribution of informative information, considering the standard of the company that changes according to market conditions at that time.